2020
DOI: 10.1096/fj.202000190rr
|View full text |Cite
|
Sign up to set email alerts
|

Duraplasty of PHBV/PLA/Col membranes promotes axonal regeneration by inhibiting NLRP3 complex and M1 macrophage polarization in rats with spinal cord injury

Abstract: Duraplasty after decompression decreases the lesion size and scar formation, promoting better functional recovery, but the underlying mechanism has not been clarified. Here, we fabricated a series of poly(hydroxybutyrate‐co‐hydroxyvalerate)/polylactic acid/collagen (PHBV/PLA/Col) membranes and cultured them with VSC4.1 motor neurons. The material characteristics and in vitro biological characteristics were evaluated. In the subcutaneous implantation test, PHBV/PLA/COl scaffolds supported the cellular infiltrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Therefore, the abuse of N2O may cause long-term and irreversible damage to neurons and movement. Lately, two studies have shown that the depression of the activation of NLRP3 inflammasomes can be beneficial for axonal regeneration of nerve cells [ 35 , 36 ]. This suggests that the therapeutic effect of TXNIP/NLRP3 knockdown on N2O-induced nerve injury may be connected with axonal regeneration, which needs to be further explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the abuse of N2O may cause long-term and irreversible damage to neurons and movement. Lately, two studies have shown that the depression of the activation of NLRP3 inflammasomes can be beneficial for axonal regeneration of nerve cells [ 35 , 36 ]. This suggests that the therapeutic effect of TXNIP/NLRP3 knockdown on N2O-induced nerve injury may be connected with axonal regeneration, which needs to be further explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that duroplasty with PHBV/PLA/Collagen membranes reduced glial scar formation and promoted axonal growth by inhibiting inflammasome activation and modulating macrophage polarization in acute SCI. Functional locomotor recovery improved 8 weeks after injury [82].…”
Section: Phbv Composites For Tissue Engineering Applicationsmentioning
confidence: 91%
“…For example, it has been shown that poly(3-hydroxybutyrate-co-3-hydroxyvalerate)/ collagen (PHBV/Col) nanofibers are promising substrates as bioengineered grafts for the regeneration of neural tissue [ 137 , 138 ]. Zhao and his colleagues found that the use of poly(hydroxybutyrate-co-hydroxyvalerate)/polylactic acid/ collagen (PHBV/PLA/Col) membranes for duralplasty reduced glial scar formation and promoted axonal regeneration after acute SCI by suppressing NLRP3 inflammasome activation and M1 macrophage polarization [ 139 ]. In addition, ceria nanoparticle (CeNP) has been shown to attenuate WMI after ICH, and the mechanisms may be related to the involvement of microglia and astrocytes in myelin regeneration [ 71 ].…”
Section: Targeting Nlrp3 In the Pathogenesis Of Secondary Wmi After Ichmentioning
confidence: 99%